Vision and development in Trichoderma atroviride - Casas S; Cortes C; Rios M; Rosales T; Bibbins M; Olmedo V; Herrera-Estrella A (浙江大学学报. 农业与生命科学版)
Phototropism, the induction of carotenogenesis and reproductive structures, and resetting of the circadian rhythm are controlled by blue light. Trichoderma is used as a photomorphogenetic model due to its ability to conidiate upon exposure to light. In total darkness, T. atroviride grows indefinitely as a mycelium provided that nutrients are not limiting. However, nutrient deprivation and light trigger the conidiation process. A pulse of blue light given to a radially growing colony induces synchronous sporulation. A ring of conidiophores bearing green conidia is produced at what had been the colony perimeter at the time of the light pulse. All known responses to blue light in N. crassa are initiated by a couple of transcription factors encoded by the white-collar genes (wc -1 and wc-2). WC-1 and WC-2 bind to the promoters of light regulated genes to rapidly activate transcription in response to light. In T. atroviride the photolyase encoding gene phr1 undergoes fast transcriptional activation in response to light. The presence of putative WCC binding boxes in the promoter of phr1, suggested that light responses in Trichoderma could be under the control of white-collar homologues. We cloned two genes and demonstrated by gene replacement that both are essential for photoconidiation and photolyase gene expression. Therefore, they were named blue-light regulator one and two (blr1 and blr2). The BLR1 protein has all the characteristics of a blue-light photoreceptor. The generation of subtractive cDNA libraries allowed us to identify novel, BLR independent, light responses including the regulation of gene expression by blue-light. In addition, we recently initiated a Trichoderma ESTs sequencing project. Until now, we have sequenced above 3000 ESTs, from which we have obtained approximately 1800 unigenes. This unigene set was printed in microarrays and used to search for light induced genes. Twenty five clearly induced and around thirty repressed genes have been detected. Among this set we have found both blr dependent and independent blue light induced genes, strengthening our view of the existence of alternative light perception pathways. We also show the first evidence for the entry of Trichoderma into the conidiation process caused by mechanical injury, which remains unaltered in the mutants. Finally, an unprecedented crosstalk between light and glucose sensing was found involving the BLR1 and BLR2 proteins in the control of carbon deprivation induced conidiation.